Изучение полета птиц на Украине. Сообщение 1. Исследование свободного полета - Цвелых, А.Н. (Вестник зоологии, 1993)
Significant correlation between flight speed and wingbeat frequency in 12 bird species is established. Fine wingbeat kinematic structure have been studied in coot. A new parameter — relative step — is suggested to characterize the bird flight ability. In flight speed range mostly common in birds, the relation between energy expenditure and flight speed is in approximate to direct line. The correlations between the energy expenditure and wingbeat frequency in Laridae and Corvidae is found. A. B. Kistyakovsky was first who suggested the screen effect to be used by birds. Original model based experiments and theoretical analysis have led to a conclusion that flight over a wavy surface is not less effective than that over a flat one. Measurements of bird flight characteristics over the water surface show a certain energetic advantage (15%) of the screen effect use. The air speed is found to be linearly increasing in headwing and usually decreasing in tailwind. The wind drift compensation increased along with wing load increaso. The wingbeat frequency linearly decreases in headwind, in tailwind it varies slightly. The flight in a wind tunnel represents a peculiar combination of flight conditions appearing in headwind and still air conditions. A bird is suggested to obtain wind direction information upon interaction of the flapping wing and air flow — this phenomenon is to explain a mysterious ability of the flying bird to determine the wind direction without terrestrial landmarks.